Antioxidant activity of ten grades of Indonesia black tea (Camellia sinensis (L.) O. Kuntze) liquor - Sudaryat, Yayat; Kusmiyati, Mimin; Pelangi, Citra Ratu; Rustamsyah, A; Rohdiana, Dadan (Jurnal Penelitian Teh dan Kina, 2015)
Tea is one kind of plant that is popular as a beverage. These plants contain antioxidant potential of flavonoids derived from polyphenol compounds. The research aimed to examine the antioxidant activity and to determine the con-tent of total phenols and total flavonoids from ten grades of Indonesian black tea liqour. Antioxidant activity was measured by the method of free radical scavenging by DPPH, total phenol content measured by Follin-Ciocalteu method, and total flavonoid content was measured by the method of AlCl3. The results of this research showed that The highest total phenol content contained in Dust III withÂ 225,80 mgGAE/100 g and the lowest content is BTL with 111,26 mgGAE/100 g. The test results showed that BBL has the highest total flavonoid content with 0,151 mg/g, while the lowest is BTL flavonoid with 0,086 mg/g. Meanwhile the highest antioxidant activity of ten grade of Indonesian black tea infusion obtained by Dust I, with IC50 97,00 Î¼g/ml. Meanwhile the lowest antioxidant activity with IC50 178,56 Î¼g/ml was obtained by BTL.